A plot of one's own: gender relations and irrigated land allocation policies in Burkina Faso - Zwarteveen, M.Z. (International Irrigation Management Institute, 1996)
Explores the effects of plots allocation on women's labor contributions in the Dakiri irrigation system of Burkina Faso. Compares intra-household distribution of income derived from agricultural activities when men are the sole owners of plots to income distribution when both men and women within the same household own irrigated plots.